Nucleotide sequence variant of the TPM1 gene in a family with different phenotypes of left ventricular non-compaction - M. M. Kudryavtseva; A. V. Kiseleva; R. P. Myasnikov; O. V. Kulikova; A. N. Meshkov; E. A. Mershina; R. K. Angarsky; Е. A. Sotnikova; M. G. Divashuk; A. A. Zharikova; S. N. Koretsky; D. A. Filatova; et al. (Кардиоваскулярная терапия и профилактика, 2023)
Left ventricular non-compaction (LVNC) is a rare, genetically and phenotypically heterogeneous disease, which is often accompanied by diagnostic difficulties.Aim. To demonstrate several generations of a family with LVNC with various clinical and phenotypic manifestations of the disease (dilated and isolated types of LVNC) with an identified rs397516387 variant of the TPM1 gene.Material and methods. Based on the multicenter registry "Myocardial Non-compaction", a family with a familial form of LVNC was selected. Next generation sequencing (NGS) was performed on an Ion S5 system (Thermo Fisher Scientific, USA) using Ampliseq technology. Variant was verified using Sanger sequencing on an Applied Biosystem 3500 Genetic Analyzer (Thermo Fisher Scientific, USA). For clinical interpretation, variants in the genes associated with LVNC with a minor allele frequency <0,1% were selected in the gnomAD database (v2.1.1). Results. Variant rs397516387 was found in 5 family members, including the proband. Further examination revealed LVNC in 2 additional family members. The proband and the proband’s uncle had a dilated type of LVNC, and the proband’s mother had an isolated type.Conclusion. The paper presents several generations of a family with different phenotypic manifestations of LVNC and rs397516387 variant in the TPM1 gene. The beginning of genetic screening from a proband, a thorough collection of a family history and further detailed genetic screening of relatives led to the identification of rs397516387 variant in 4 more family members, which in turn made it possible to conduct an additional examination to confirm the diagnosis and prescribe timely drug therapy.